2016
DOI: 10.1111/1365-2656.12506
|View full text |Cite
|
Sign up to set email alerts
|

Larval traits carry over to affect post‐settlement behaviour in a common coral reef fish

Abstract: Most reef fishes begin life as planktonic larvae before settling to the reef, metamorphosing and entering the benthic adult population. Different selective forces determine survival in the planktonic and benthic life stages, but traits established in the larval stage may carry over to affect post-settlement performance. We tested the hypothesis that larval traits affect two key post-settlement fish behaviours: social group-joining and foraging. Certain larval traits of reef fishes are permanently recorded in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 58 publications
(153 reference statements)
0
28
2
Order By: Relevance
“…The samples used in this study were collected by Dingeldein & White (2016), and additional details of collection are provided there. Recently settled juvenile bluehead wrasse were collected using hand nets and clove oil anesthetic from three sites on the northwest shore of St. Croix, USVI (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The samples used in this study were collected by Dingeldein & White (2016), and additional details of collection are provided there. Recently settled juvenile bluehead wrasse were collected using hand nets and clove oil anesthetic from three sites on the northwest shore of St. Croix, USVI (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bluehead wrasse settle to the reef in approximately week-long pulses following a new moon (Caselle & Warner, 1996); collections for this study occurred during settlement pulses in July and August of 2012. Dingeldein & White (2016) described collecting two sets of fish: zero-day collections, in which larvae settling to a transect were collected on their first day after emergence onto the reef, and additional collections in which entire groups and solitary fish were selected haphazardly for collection after they had been on the reef for 1-4 days (age could be ensured because the transects were cleared of all fish on day 0, and tagging has shown that fish do not move between shelter crevices after emergence; White & Warner, 2007a). We used the latter set of collections to examine patterns of post-settlement growth.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations